2005
DOI: 10.1007/s10194-005-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients with headache and functional dyspepsia present meal–induced hypersensitivity of the stomach

Abstract: IntroductionFunctional gastrointestinal disorders are frequently characterised by the presence of extra-intestinal symptoms. A survey on irritable bowel syndrome showed that gynaecological, urinary, psychological, dermatological and neurological symptoms were significantly more prevalent in patients than in controls [1]. Headache, in particular, was present in more than 30% of patients suffering from this condition. Although there is no similar evaluation for functional dyspepsia, the presence of headache also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…A small observational study in Italy [21] aimed to discover the rationale for this apparent association, and found that migraineurs with functional dyspepsia could be characterized by their hypersensitivity to gastric distention and a lower discomfort threshold after meals when compared to both dyspeptics without migraine and healthy volunteers. Furthermore, clinical case studies have concluded that gastric reflux disorders can trigger migraine headache originating from specific locations [22].…”
Section: Discussionmentioning
confidence: 99%
“…A small observational study in Italy [21] aimed to discover the rationale for this apparent association, and found that migraineurs with functional dyspepsia could be characterized by their hypersensitivity to gastric distention and a lower discomfort threshold after meals when compared to both dyspeptics without migraine and healthy volunteers. Furthermore, clinical case studies have concluded that gastric reflux disorders can trigger migraine headache originating from specific locations [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytokines are also locally produced in the brain, especially in the hypothalamus, and thus may contribute to the development of anorexic, pyrogenic, somnogenic and behavioural effects [38]. Neurological problems such as phobic disorders, migraine, chronic fatigue syndrome, autism and others are examples of stress-related disorders in which phagocytic immune deficits, increased oxidative stress, endotoxemia, exaggerated levels of proinflammatory cytokines and altered gastrointestinal function have been detected [39,40]. As a supplement to the traditional treatment of neurological diseases, probiotic diet may elevate the efficiency of detoxification, immunomodulation and prevention of astrogliosis.…”
Section: Discussionmentioning
confidence: 98%
“… 4 , 32 It is postulated that migraine patients with functional dyspepsia may have increased hypersensitivity to gastric distention and reduced tolerance to food compared to healthy people. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Gastric reflux has been reported to precipitate attack of migraine. 34 Further Autonomic nervous system (ANS) dysfunction can play an important role in the etiology of both disorders. 35 - 36 …”
Section: Discussionmentioning
confidence: 99%